Chemical Consequences of the Mechanical Bond: A Tandem Active Template‐Rearrangement Reaction. Issue 12 (14th February 2019) - Modicom, Florian; Jamieson, Ellen M. G.; Rochette, Elise; Goldup, Stephen M.
Abstract: We report the unexpected discovery of a tandem active template CuAAC‐rearrangement process, in which N2 is extruded on the way to the 1, 2, 3‐triazole product to give instead acrylamide rotaxanes. Mechanistic investigations suggest this process is dictated by the mechanical bond, which stabilizes the Cu I ‐triazolide intermediate of the CuAAC reaction and diverts it down the rearrangement pathway; when no mechanical bond is formed, the CuAAC product is isolated. Abstract : A mechanical fork in the road : The unexpected discovery of a tandem active template CuAAC‐rearrangement process is reported, in which N2 is extruded on the way to the 1, 2, 3‐triazole product to give instead acrylamide rotaxanes. Mechanistic investigations suggest this process is dictated by the mechanical bond, which allows the protonation of an OH leaving group in preference to the reactive Cu−C bond, triggering the rearrangement.